2016
DOI: 10.1890/15-0252
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interactions influence feeding and anti‐predator behavior in wild and transgenic coho salmon

Abstract: Environmental conditions are known to affect phenotypic development in many organisms, making the characteristics of an animal reared under one set of conditions not always representative of animals reared under a different set of conditions. Previous results show that such plasticity can also affect the phenotypes and ecological interactions of different genotypes, including animals anthropogenically generated by genetic modification. To understand how plastic development can affect behavior in animals of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Other studies have also demonstrated a survival advantage of T MT over W fish in severe growth-limiting conditions [20, 21]. Due to low anti-predator behavior observed in T MT strain fish [31, 32], GH transgenic fish are expected to have lower survival than W fish under predation pressure, as has been observed in some studies [20, 33], but not others [21]. T MT fry had inconsistent relative survival in the presence of predators, where survival was higher than W fry at medium food levels in Exp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also demonstrated a survival advantage of T MT over W fish in severe growth-limiting conditions [20, 21]. Due to low anti-predator behavior observed in T MT strain fish [31, 32], GH transgenic fish are expected to have lower survival than W fish under predation pressure, as has been observed in some studies [20, 33], but not others [21]. T MT fry had inconsistent relative survival in the presence of predators, where survival was higher than W fry at medium food levels in Exp.…”
Section: Discussionmentioning
confidence: 99%
“…3. Difference in rank survival of T MT and W fry within experiments may be due to increased foraging and decreased predator avoidance behavior observed in GH transgenic fish [27, 31, 32, 3436], providing advantages or disadvantages to T MT fry depending on food availability and predator presence. The factors causing differences in rank order among equal conditions in different studies are not known, but could include age and relative size at entry, length of trial, competitive ability of different co-habiting T H3 strains, and/or amount of refuge areas in substrate (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, the existence of transgenic species offers a good tool to study this problem. By comparing wild-type siblings and transgenic individuals, Sundström et al [50] found that wild and transgenic animals behave in the manner under natural like conditions; but until now, there are not a sufficient number of studies to conclude that genetically modified organisms are not affected by the complexity of natural conditions.…”
Section: Predator Avoidance Behaviourmentioning
confidence: 99%
“…The feeding behaviour of animals is complex and the acts of feeding and ingestion are the final results of a number of factors between the animal and its ecological interactions (Sundstrom et al, 2016). Neuropeptide Y (NPY), a 36 amino acid peptide, is one of the most conserved neuroendocrine peptides (Larhammar, 1996) and is known to be involved in the regulation of feeding behaviour in mammals (Schwartz et al, 1993;Stanley, 1993;Kaiyala et al, 1995), amphibians (Crespi et al, 2004) as well as in fish (Subhedar, 2006;Volkoff, 2016;Yan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%